Carbon ceramic coating brake disc with net size and low cost and preparation method thereof

The carbon cloth mesh tire composite layer was prepared by alternate laying and engraving holes, which solved the problems of long fiber carbon ceramic coating brake disc production cycle and low material utilization rate, and achieved low cost and high performance carbon ceramic coating The layer brake disc is suitable for passenger cars and rail transit fields.

CN119241250APending Publication Date: 2025-01-03HUNAN SHIXIN NEW MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411323811.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing long-fiber carbon ceramic coating brake disc has a long production cycle, high processing difficulty, and low material utilization rate, resulting in high cost and difficult to apply in the field of rail transit, and lack of wear resistance and oxidation resistance.

Method used

The carbon cloth mesh composite layer is prepared by alternately laying a layer of carbon cloth and a layer of carbon fiber mesh. The circular holes are engraved to form a porous carbon cloth mesh composite layer, and the porous circle is prepared by winding it on a rod-shaped mold for continuous needle puncture. The cylinder-type preformed body is divided into a preformed body disc in the axial direction, and undergoes chemical vapor deposition and melt-silicon seepage, and introduces wear-resistant coatings to improve performance.

Benefits of technology

It greatly shortens the production cycle, improves material utilization, reduces costs, improves product competitiveness, and enhances the wear resistance and oxidation resistance of carbon ceramic coated brake discs. It is suitable for a wider range of passenger cars and rail transit applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241250A_ABST
    Figure CN119241250A_ABST
Patent Text Reader

Abstract

The invention discloses a net-size low-cost carbon ceramic coating brake disc and a preparation method thereof.The preparation method comprises the steps that a carbon cloth net tire composite layer is obtained in the mode that a layer of carbon cloth and a layer of carbon fiber net tire are alternately laid, and then round holes are carved in the carbon cloth net tire composite layer to form a porous carbon cloth net tire composite layer; meanwhile, the porous carbon cloth net tire composite layer is wound on a rod-shaped mold to be continuously needled to prepare a porous cylindrical prefabricated body; the preparation method comprises the following steps: cutting a cylindrical preform into a plurality of preform discs containing ventilating ducts along the axial direction of the cylindrical preform, performing chemical vapor deposition densification to obtain a carbon-carbon green body, arranging a carbon coating on the end surface of the carbon-carbon green body to obtain a carbon-carbon coating green body, and then melting and siliconizing the carbon-carbon coating green body to obtain the carbon-carbon coating silicon carbide ceramic. According to the method, the processing time of the carbon-ceramic brake disc is shortened, the utilization rate of carbon fibers is increased, and the stable friction coefficient and wear resistance are provided. The structural design is reasonable, the preparation process is simple and controllable, the obtained product is excellent in performance, and large-scale industrial application is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of passenger car and rail transit brake discs, and in particular relates to a net-size, low-cost carbon-ceramic coating brake disc and a preparation method thereof. Background Art

[0002] At present, with the increasing application of carbon-ceramic brake discs, the pursuit of lower costs and better performance has become the top priority of industry competition.

[0003] At present, the representative of low cost in China is short fiber molded disc, but due to the limitation of mechanical properties, molded disc can only be used in some passenger cars with not particularly bad working conditions, let alone in the field of rail transportation. The high-performance long fiber carbon ceramic brake disc has high cost due to its complicated process, long production cycle, difficult processing, low material utilization rate and other problems. In addition, the market generally recognizes and accepts carbon ceramic coated brake discs with better wear resistance, oxidation resistance and appearance, which makes the production process more complicated and the cost more difficult to reduce. Summary of the invention

[0004] In view of the problems of long production cycle, great processing difficulty and low material utilization rate of long fiber carbon ceramic coated brake disc in the prior art, the first object of the present invention is to provide a method for preparing a carbon ceramic coated brake disc with low net size and low cost. The preparation method of the present invention can significantly shorten the production cycle, reduce the processing amount and improve the material utilization rate to reduce the overall cost, thereby improving the competitiveness of the product.

[0005] The second object of the present invention is to provide a carbon-ceramic coated brake disc prepared by the above preparation method.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] The invention discloses a method for preparing a carbon-ceramic coating brake disc with a net size and low cost. The method comprises the following steps: obtaining a carbon cloth mesh composite layer by alternately laying a layer of carbon cloth and a layer of carbon fiber mesh, controlling the total number of carbon cloth layers to be N layers and the total number of carbon fiber mesh layers to be M layers, then carving circular holes on the carbon cloth mesh composite layer to form a porous carbon cloth mesh composite layer, and simultaneously winding the porous carbon cloth mesh composite layer on a rod-shaped mold and continuously needle-punching the porous cylindrical preform; dividing the cylindrical preform into a plurality of preform discs containing ventilation ducts along the axial direction of the porous cylindrical preform, performing chemical vapor deposition densification on the preform disc containing the ventilation duct to obtain a carbon-carbon blank, providing a carbon coating on the end face of the carbon-carbon blank to obtain a carbon-carbon coating blank, and then subjecting the carbon-carbon coating blank to melt siliconization to obtain a carbon-ceramic coating brake disc.

[0008] The preparation method of the present invention divides the cylindrical preform into a plurality of preform discs containing ventilation ducts along the axial direction of the porous cylindrical preform. Since the fiber direction is changed, on the one hand, circular holes can be engraved during the preparation of the preform to form the ventilation duct of the brake disc, which greatly reduces the cost of CNC-forming the carbon-carbon blank or the finished brake disc to open the ventilation duct in the later stage. On the other hand, due to the existence of the ventilation duct and the change of the fiber direction, the deposition efficiency of the chemical vapor deposition can be greatly improved, and the uniformity of the chemical vapor deposition can be improved. In addition, in order to compensate for the change in the fiber direction, the present invention introduces a wear-resistant coating, thereby avoiding the problems of non-wear resistance and unstable friction coefficient of the carbon-ceramic brake disc caused by changing the fiber direction.

[0009] In a preferred embodiment, both N and M are 2-4, preferably 3. The inventors have found that controlling the number of carbon cloth and carbon fiber mesh within the range of 2-4 layers has the lowest cost and the best performance, while if the number of layers is too low, the production and processing time will increase significantly, and if the number of layers is too high, it is difficult to ensure the needling effect and interlayer cracks are likely to occur.

[0010] A preferred solution is to control the size of the engraved circular holes to be consistent when engraving the circular holes on the carbon cloth mesh composite layer, and the spacing between the circular holes on the carbon cloth mesh composite layer increases as the diameter increases according to its position in the cylindrical preform, so as to ensure that all the circular holes on the same radius in the cylindrical preform are coaxial after winding.

[0011] The solution of the present invention can perform drilling at the preform layer laying stage, which not only greatly reduces the difficulty and cost of drilling, but also further improves the efficiency and uniformity of chemical vapor deposition.

[0012] In a preferred embodiment, the engraving of the circular holes is performed simultaneously with the continuous needling process.

[0013] In the actual operation, N layers of carbon cloth and M layers of carbon fiber mesh with a certain length and width are taken and alternately laid to form a carbon cloth mesh composite layer. Then, circular holes are carved on the carbon cloth mesh composite layer, and the carved layer is cleaned off during the carving process. At the same time, the portion of the carbon cloth mesh composite layer with the carved circular holes is wound and needled continuously. The efficiency is greatly improved by simultaneously carving circular holes on the carbon cloth mesh composite layer and needled the preform.

[0014] In a preferred solution, the diameter of the circular hole in the cylindrical preform is 8-30 mm, and the opening rate is 1-10%.

[0015] In the present invention, the diameter of the circular hole of the cylindrical preform is adjusted within the above diameter range according to the requirements of the thickness and size of the finished disk.

[0016] In a preferred embodiment, the porous carbon cloth web composite layer is continuously needled and spread into a flat surface with a thickness of 1.5-3.0 mm.

[0017] In a preferred embodiment, the density of the cylindrical preform is 0.5-0.6 g / cm 3 , preferably 0.53-0.57 g / cm 3 .

[0018] By controlling the density of the final cylindrical preform within the above range, the performance of the final carbon-ceramic coated brake disc is optimal. If the density is low, the fiber content is low, and the mesh tread density generally used is low, which will lead to insufficient interlayer strength, and the subsequent deposition cost and time will also increase; high density will cause the preform to be very compact and the internal porosity to be uneven, which will reduce the carbon utilization rate of the carbon source gas during the vapor deposition process.

[0019] In actual operation, the cylindrical preform is divided into preform discs according to the thickness of the finished brake disc.

[0020] In a preferred embodiment, the cylindrical preform is first subjected to high temperature heat treatment and then subjected to chemical vapor deposition densification, wherein the temperature of the high temperature heat treatment is 1700-2200° C., preferably 2000° C. In actual operation, the preform disk is subjected to high temperature heat treatment under a protective atmosphere to eliminate impurities, remove needle puncture stress, and obtain more uniform internal pores.

[0021] In a preferred embodiment, during the chemical vapor deposition densification, the dilution gas is nitrogen and the carbon source gas is natural gas, wherein the ratio of nitrogen to natural gas is 1:1-4, preferably 1:2.

[0022] In the present invention, natural gas with the lowest cost is used as the carbon source gas, which can obtain a good deposition effect, high deposition uniformity, high efficiency and short time.

[0023] In a preferred embodiment, the temperature of the chemical vapor deposition is 900° C.-1100° C., preferably 1050-1100° C., and the time of the chemical vapor deposition is 120-150 hours.

[0024] In the present invention, only 120-150 hours of deposition is required to obtain the density achieved by 200 hours of deposition in the traditional scheme.

[0025] After the preform needling method was changed, the carbon utilization rate in the deposition process increased from about 28% to about 35%, reducing the use of carbon source gas and simultaneously reducing the time of chemical vapor deposition; the residual dynamic unbalance of the carbon-ceramic coated brake disc was improved from the original 0.5-6.0g·m fluctuation to a stable level within 3.0g·m, and the uniformity of deposition and infiltration was greatly improved.

[0026] In a preferred embodiment, the density of the carbon-carbon blank is 1.30-1.45 g / cm 3 .

[0027] In a preferred embodiment, the carbon coating is provided by molding the carbon coating raw material powder into the end surface of the carbon-carbon blank, wherein the carbon coating raw material powder is composed of the following components by weight: 30-50 parts of phenolic resin powder, 30-50 parts of silicon carbide mixed powder, 10-30 parts of silicon powder, and 3-5 parts of carbon black;

[0028] The silicon carbide mixed powder is composed of the following parts by mass: 17-25 parts of silicon carbide powder A with a particle size of 60-200 meshes, 10-17 parts of silicon carbide powder B with a particle size of 400-800 meshes, and 3-8 parts of silicon carbide powder C with a particle size of 1000-2000 meshes.

[0029] The carbon coating of the present invention is molded into the end face (friction face) of the carbon-carbon blank in the form of powder. The carbon coating powder raw material uses silicon carbide powders of different particle sizes to stabilize the friction coefficient, reduce disc wear, and reduce the probability of jitter during braking. Silicon powder is mainly used to enhance the effect during the infiltration process and promote ceramicization. The added carbon black has better activity than carbon powder and graphite powder, and can also promote the silicon-carbon reaction during the infiltration process. At the same time, the cost of carbon black is lower.

[0030] Further preferably, the thickness of the carbon-carbon coating formed by molding the carbon coating raw material powder into the end surface of the carbon-carbon blank is 1-3 mm, preferably 1.5 mm (1.0 mm after finished product processing).

[0031] Further preferably, the carbon coating raw material powder is composed of the following parts by mass: 40 parts of phenolic resin powder, 40 parts of silicon carbide mixed powder, 15 parts of silicon powder, and 5 parts of carbon black.

[0032] Further preferably, the silicon carbide mixed powder is composed of the following parts by mass: 20 parts of silicon carbide powder A with a particle size of 80-100 mesh, 15 parts of silicon carbide powder B with a particle size of 400-600 mesh, and 5 parts of silicon carbide powder C with a particle size of 1200-1500 mesh.

[0033] Further preferably, the carbon black is the carbon black powder produced in the chemical vapor deposition process, which is crushed and then passed through a 400-mesh sieve.

[0034] In a preferred embodiment, the temperature of the molten siliconizing is 1600-1900° C., preferably 1800° C., the time is 1-4 hours, preferably 2 hours, and the pressure is below 200 Pa.

[0035] In actual operation, molten siliconizing uses silicon powder as the silicon source, and slowly increases the temperature during the low-temperature heating stage to carbonize the coating to ensure the quality of the coating.

[0036] The present invention also provides a carbon-ceramic coating brake disc prepared by the above preparation method.

[0037] In a preferred embodiment, the density of the carbon-ceramic coating brake disc is 2.00-2.50 g / cm 3 , the opening rate is 1-10%, the interlaminar shear strength is 80-120MPa, the compressive strength is 180-240MPa, the flexural strength is 120-180MPa, and the impact toughness is 20-40KJ / m 2 .

[0038] Beneficial Effects

[0039] Taking the automobile disc as an example, the present invention uses the needle-punched cylinder technology to replace the needle-punched flat plate technology to prepare the preformed disc. The original carbon fiber utilization rate in the process from the needle-punched flat plate to the preformed disc is about 50%; the present invention uses a wooden mold in the core of the cylinder, which reduces the waste of carbon fiber in the middle round cake and the four corners in the process from the needle-punched cylinder to the preformed disc, and the carbon fiber utilization rate is increased to about 95%. The fiber saving reduces the production cost of the carbon-ceramic coated brake disc by 5%.

[0040] Taking the automobile disc as an example, the time consumed for engraving circular holes on the carbon fiber cloth + carbon fiber mesh composite layer of the present invention is about 0.25h per disc, while the traditional CNC air duct processing time for a single disc is about 2.0h; the engraving of circular holes on the carbon fiber cloth + carbon fiber mesh composite layer of the present invention and the needle-punching of the preform cylinder can be carried out simultaneously, the height of the cylinder can reach 1.4m, and it can be divided into more than 30 preform discs, so the production of one preform cylinder can greatly reduce the CNC processing time.

[0041] The reserved ventilation duct of the preform disc of the present invention reduces the volume by about 10%, and correspondingly saves about 10% of the chemical vapor deposition time, carbon source gas, nitrogen, power consumption, etc.; and reduces the production cost of the carbon-ceramic coated brake disc by 2% overall.

[0042] In the process of chemical vapor deposition, the present invention reduces the resistance encountered by the carbon source gas when entering the internal pores of the preform disc from bottom to top due to the change in the fiber arrangement direction and the reserved ventilation duct, and the carbon utilization rate of the carbon source gas is increased from the original 28% to about 35%, and the chemical vapor deposition time, carbon source gas, nitrogen, power consumption, etc. are all saved by about 20%; the overall production cost of the carbon-ceramic coated brake disc is reduced by 4%.

[0043] The residual dynamic unbalance of the carbon-ceramic coating brake disc of the present invention is ≤3.0 g·m, which eliminates the production cost of debonding and reworking, reduces the process steps, and improves the smoothness of product production.

[0044] Compared with the prior art, the present invention has the following advantages:

[0045] (1) The amount of carbon fiber used is reduced by about 47.5%.

[0046] (2) The reservation of ventilation ducts for the preform disk reduces the volume by about 10%, and saves about 10% of the synchronous chemical vapor deposition time, carbon source gas, nitrogen, power consumption, etc.

[0047] (3) The carbon utilization rate during chemical vapor deposition is increased from 28% to about 35%, and the synchronous chemical vapor deposition time, carbon source gas, nitrogen, and power consumption are all saved by about 20%.

[0048] (4) The introduction of the coating solves the problems of poor wear resistance and unstable friction coefficient of the carbon-ceramic brake disc under this preparation scheme.

[0049] (5) The net size of the ventilation duct reserved greatly reduces the processing time.

[0050] (6) The more uniform chemical vapor deposition and molten siliconization under this preparation scheme result in a lower residual dynamic unbalance. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 It is a schematic diagram of a cylindrical preform;

[0052] Figure 2 This is a schematic diagram of the carbon cloth mesh composite layer after engraving circular holes;

[0053] Figure 3 This is a schematic diagram of the carbon cloth mesh composite layer after engraving circular holes;

[0054] Figure 4 It is a schematic diagram of cutting a carbon fiber preform in the prior art.

[0055] Figure 5 is a schematic diagram of a carbon fiber preform in the prior art;

[0056] Figure 6 It is a schematic diagram of cutting a cylindrical preform into a preform disk according to the present invention;

[0057] Figure 7 is a schematic diagram of a preform disc in the present invention;

[0058] Figure 8 This is the direction of mechanical property testing in the present invention. DETAILED DESCRIPTION

[0059] Example 1

[0060] (1) Three layers of carbon cloth and three layers of mesh tire are laid together alternately to form a carbon cloth mesh tire composite layer.

[0061] (2) Carving circular holes in the carbon cloth mesh composite layer, controlling the diameter of the circular holes to be 15 mm, and the spacing between the circular holes on the carbon cloth mesh composite layer increases with the diameter according to the position of the circular holes in the cylindrical preform, so as to ensure that all the circular holes on the same radius in the cylindrical preform are coaxial after winding,

[0062] (3) During the engraving process, the engraved layer is cleaned off, and the portion of the carbon cloth mesh composite layer with engraved circular holes is wound around a wooden rod-shaped mold and continuously needled. The needle-punched preparation density is 0.55 g / cm 3 Preform cylinder;

[0063] (4) dividing the preform cylinder into preform discs,

[0064] (5) The preform disk is heat treated at 2000°C under argon atmosphere.

[0065] (6) The preform disk after high temperature heat treatment was introduced into nitrogen and natural gas at 1080°C, with the ratio of nitrogen to natural gas being 1:2, and chemical vapor deposition densification was performed for 130 hours until the density was 1.35 g / cm 3 Get carbon-carbon brake discs.

[0066] (7) molding 1.5 mm carbon / silicon carbide coating powder on both end surfaces of a carbon-carbon brake disc to obtain a carbon-carbon coated brake disc, wherein the carbon / silicon carbide coating powder is composed of the following components by weight: 40 parts of phenolic resin powder, 40 parts of silicon carbide mixed powder, 15 parts of silicon powder, and 5 parts of carbon black;

[0067] The silicon carbide mixed powder is composed of the following parts by mass: 20 parts of silicon carbide powder A with a particle size of 80-100 meshes, 15 parts of silicon carbide powder B with a particle size of 400-600 meshes, and 5 parts of silicon carbide powder C with a particle size of 1200-1500 meshes.

[0068] (8) Processing and shaping according to product drawings.

[0069] (9) A carbon-carbon coated brake disc is melt-siliconized at 1800°C and below 200 Pa for 2 h to obtain a carbon-ceramic coated brake disc.

[0070] In this embodiment, steps (1) to (4) take a total of 12 hours to cut 34 automotive discs; step (6) loads 12 discs into the furnace for a total of 136 hours of vapor deposition (excluding heating and cooling time); and step (8) takes 2 hours to process each disc.

[0071] Steps (1) to (4) use a total of 70.86 kg of fiber to cut 34 automotive discs, with an average of 2.08 kg of fiber per disc. Step (6) uses a total of 116.57 kg of natural gas and 102 kg of nitrogen to load 12 discs into the furnace.

[0072] The carbon-ceramic coating brake disc prepared in this example has a density of 2.42 g / cm 3 The opening rate is 1.05%, the residual dynamic unbalance is 1.36g·m, the shear strength is as high as 102.13MPa, the compressive strength of the carbon-ceramic composite material support layer is 225.56MPa, the flexural strength is 145.34MPa, and the impact toughness is 35.32KJ / m 2 , this performance far meets the use requirements.

[0073] In the friction and wear test of the carbon-ceramic coating brake disc matched with the brake pad in this embodiment, the friction coefficient is stable, the carbon-ceramic coating brake disc is basically free of wear, and the surface is flat and undamaged.

[0074] Example 2

[0075] The difference between this embodiment and Embodiment 1 is that two layers of carbon cloth and two layers of web are alternately laid together to form a carbon cloth web composite layer.

[0076] In this embodiment, steps (1) to (4) take a total of 16 hours to cut 34 automobile plates; because the number of layers of the carbon cloth mesh composite layer is reduced, the time for engraving the circular holes is increased by 50%.

[0077] Example 3

[0078] The difference between this embodiment and Embodiment 1 is that 4 layers of carbon cloth and 4 layers of web are alternately laid together to form a carbon cloth web composite layer.

[0079] In this embodiment, steps (1) to (4) take a total of 10 hours to cut 34 automobile plates; because the number and thickness of the carbon cloth mesh composite layer are increased, the difficulty of cleaning the engraving waste when engraving the round hole is increased.

[0080] Comparative Example 1

[0081] (1) It is made of 1 layer of carbon fiber non-woven fabric and 1 layer of carbon fiber mesh fabric by continuous needle punching. The non-woven fabric is laid at 0° / 90°. The needle punching density is 0.55g / cm 3 Prefabricated flat plate.

[0082] (2) Divide the preform flat plate into preform disks.

[0083] (3) The preform disk is heat treated at 2000°C in an argon atmosphere.

[0084] (4) The preform disk after high temperature heat treatment was introduced into nitrogen and natural gas at 1080°C, and chemical vapor deposition was used to increase the density to 1.35 g / cm 3 Get carbon-carbon brake discs.

[0085] (5) A 1.5 mm phenolic resin + silicon carbide coating is molded on both end surfaces of a carbon-carbon brake disc to obtain a carbon-carbon coated brake disc.

[0086] (6) Processing and forming according to product drawings.

[0087] (7) The carbon-carbon coated brake disc is melt-siliconized at 1800°C and below 200 Pa for 2 h to obtain a carbon-ceramic coated brake disc.

[0088] In this comparative example, steps (1) to (2) took a total of 15 hours to cut 9 automobile discs; step (4) loaded the furnace with 12 discs for vapor deposition for a total of 190 hours (excluding heating and cooling time); and step (6) took 4.5 hours to process each disc.

[0089] Step (1) to step (2) cut 9 automobile discs and used a total of 34.35 kg of fiber, with an average of 3.82 kg of fiber per disc. Step (4) loads 12 discs into the furnace and consumes a total of 162.86 kg of natural gas and 142.50 kg of nitrogen.

[0090] The carbon ceramic coating brake disc prepared in this comparative example has a density of 2.35 g / cm 3 The opening rate is 1.35%, the residual dynamic unbalance is 3.46g·m, the shear strength is as high as 14.58MPa, the compressive strength of the carbon-ceramic composite material support layer is 300.55MPa, the flexural strength is 149.34MPa, and the impact toughness is 37.54KJ / m 2 The comparative disc has better performance except for the lower shear strength, but the overall production cost and production cycle are greatly increased, so it is not advantageous in comprehensive evaluation.

[0091] Comparative Example 2

[0092] The difference between this comparative example and Example 1 is that the coating preparation process in step (7) of Example 1 is not performed to prepare the carbon-ceramic brake disc.

[0093] The mechanical properties of the carbon-ceramic brake disc prepared in this comparative example have a low compressive strength of only 165.23 MPa. During the friction and wear test of the carbon-ceramic brake disc matched with the brake pad, significant friction coefficient instability occurs. The carbon-ceramic brake disc also shows significant wear, surface damage and gullies.

Claims

1. A method for preparing a carbon-ceramic coated brake disc with a net size and low cost, characterized in that: A carbon cloth mesh composite layer is obtained by alternately laying a layer of carbon cloth and a layer of carbon fiber mesh, the total number of carbon cloth layers is controlled to be N layers, and the total number of carbon fiber mesh layers is controlled to be M layers, then circular holes are carved on the carbon cloth mesh composite layer to form a porous carbon cloth mesh composite layer, and at the same time, the porous carbon cloth mesh composite layer is wound on a rod-shaped mold and continuously needle-punched to prepare a porous cylindrical preform; the cylindrical preform is divided into a plurality of preform disks containing ventilation ducts along the axial direction of the porous cylindrical preform, the preform disk containing the ventilation duct is subjected to chemical vapor deposition densification to obtain a carbon-carbon blank, a carbon coating is provided on the end face of the carbon-carbon blank to obtain a carbon-carbon coated blank, and then the carbon-carbon coated blank is melt-siliconized to obtain a carbon-ceramic coated brake disc.

2. A method for preparing a carbon-ceramic coated brake disc with a net size and low cost according to claim 1, characterized in that: The N and M are both 2-4.

3. A method for preparing a carbon-ceramic coated brake disc with a net size and low cost according to claim 1 or 2, characterized in that: When engraving circular holes on the carbon cloth mesh composite layer, the size of the engraved circular holes is controlled to be consistent, and the spacing between the circular holes on the carbon cloth mesh composite layer is expanded as the diameter increases according to its position in the cylindrical preform, so as to ensure that all circular holes on the same radius in the cylindrical preform are coaxial after winding; the engraving of the circular holes is carried out simultaneously with the continuous needling process.

4. A method for preparing a carbon-ceramic coated brake disc with a net size and low cost according to claim 1 or 2, characterized in that: The diameter of the circular hole in the cylindrical preform is 8-30 mm, and the opening rate is 1-10%; The thickness of the porous carbon cloth web composite layer after continuous needling is spread into a plane and is 1.5-3.0 mm; The density of the cylindrical preform is 0.5-0.6 g / cm 3 .

5. A method for preparing a carbon-ceramic coated brake disc with a net size and low cost according to claim 1 or 2, characterized in that: The cylindrical preform is first subjected to high-temperature heat treatment and then subjected to chemical vapor deposition densification, wherein the temperature of the high-temperature heat treatment is 1700-2200°C.

6. A method for preparing a carbon-ceramic coated brake disc with a net size and low cost according to claim 1 or 2, characterized in that: During the chemical vapor deposition densification, the diluent gas is nitrogen and the carbon source gas is natural gas, wherein the ratio of nitrogen to natural gas is 1:1-4. The temperature of the chemical vapor deposition is 900° C.-1100° C., and the time of the chemical vapor deposition is 120-150 hours; The density of the carbon-carbon blank is 1.30-1.45 g / cm 3 .

7. A method for preparing a carbon-ceramic coated brake disc with a net size and low cost according to claim 1 or 2, characterized in that: The carbon coating is provided by molding the carbon coating raw material powder into the end surface of the carbon-carbon blank, wherein the carbon coating raw material powder is composed of the following components by weight: 30-50 parts of phenolic resin powder, 30-50 parts of silicon carbide mixed powder, 10-30 parts of silicon powder, and 3-5 parts of carbon black; The silicon carbide mixed powder is composed of the following parts by mass: 17-25 parts of silicon carbide powder A with a particle size of 60-200 mesh, 10-17 parts of silicon carbide powder B with a particle size of 400-800 mesh, and 3-8 parts of silicon carbide powder C with a particle size of 1000-2000 mesh; The thickness of the carbon-carbon coating formed by molding the carbon coating raw material powder into the end surface of the carbon-carbon blank is 1-3 mm.

8. A method for preparing a carbon-ceramic coated brake disc with a net size and low cost according to claim 1 or 2, characterized in that: The carbon coating raw material powder is composed of the following parts by mass: 40 parts of phenolic resin powder, 40 parts of silicon carbide mixed powder, 15 parts of silicon powder, and 5 parts of carbon black; The silicon carbide mixed powder is composed of the following parts by mass: 20 parts of silicon carbide powder A with a particle size of 80-100 mesh, 15 parts of silicon carbide powder B with a particle size of 400-600 mesh, and 5 parts of silicon carbide powder C with a particle size of 1200-1500 mesh; The carbon black is the product obtained by crushing the carbon black powder produced in the chemical vapor deposition process and passing it through a 400-mesh sieve.

9. A method for preparing a carbon-ceramic coated brake disc with a net size and low cost according to claim 1 or 2, characterized in that: The temperature of the molten siliconization is 1600-1900° C., the time is 1-4 hours, and the pressure is below 200 Pa.

10. A carbon-ceramic coated brake disc prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of high-strength charcoal / charcoal hot-pressing mould for vacuum hot-pressing furnace

    CN101797646A

  • Carbon fiber preform for carbon-ceramic brake disc as well as preparation method and application of carbon fiber preform

    CN112848543A

  • Method for improving densification density and density uniformity of carbon / carbon composite material thick plate

    CN113149648A

  • Preparation method of high-bonding-strength carbon-ceramic brake coating disc

    CN117567167A